Nanoparticle-Based mRNA Vaccine Induces Protective Neutralizing Antibodies Against Infectious Bronchitis Virus in In-Vivo Infection - Aseno Sakhrie; Ankarao Kalluri; Zeinab H. Helal; Challa V. Kumar; Mazhar I. Khan (Vaccines, 2025)
Background: Live attenuated and inactivated virus vaccines are commonly used against infectious bronchitis virus (IBV) in chickens, but they have limitations such as mutation risks and short efficacy. This study explores cationic bovine serum albumin (BSA) polyamine nanoparticles (NPs) for delivering IBV spike protein mRNA, aiming to develop a safer and more effective vaccine. Methods: A BSA-based nanoparticle system was designed with positive surface charges and characterized using dynamic light scattering (DLS), Zetasizer, and transmission electron microscopy (TEM). Its cytotoxicity, cellular uptake, and ability to deliver IBV spike protein mRNA were evaluated in macrophage-like chicken cell lines (HD11), followed by immunogenicity studies in SPF chickens to assess immune responses. Results: The study demonstrated successful binding and transfection efficiency of the in vitro transcription (IVT)-mRNA complexed with the NPs, which was enhanced with chloroquine. Immunogenicity studies in SPF chickens showed a significant increase in antibody titers in chickens vaccinated with the mRNA vaccine compared to the PBS control, indicating an effective immune response against the IBV S protein. Furthermore, the neutralization index doubled after a higher-dose mRNA booster with chloroquine, and PBMCs from immunized chickens exhibited a threefold higher stimulation index than the PBS control. Conclusions: BSA-based NPs effectively deliver IBV spike protein mRNA, enhancing immune responses and offering a promising strategy for a safer, more effective IBV vaccine.